Study guides

☆☆

Q: How do you factor the expression 30 plus 12x equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

As written, this expression equals 22x + 3, which doesn't factor neatly. Make sure you copied it correctly.

(2x + 3)(2x + 3)

(x-3)(x-9) = 0

2(x - 2)(x - 4)

12x + 5 - 2x =(12x - 2x) + 5 =10x + 5 =5 (2x + 1)

Related questions

As written, this expression equals 22x + 3, which doesn't factor neatly. Make sure you copied it correctly.

(2x + 3)(2x + 3)

Factor 2x plus 12x plus 28 is (x - 3)(x - 9)

Without an equality sign the given expression is not an equation and so therefore finding the value of x is not possible.

The expression can be factored as -12x + 32y -16z = 4(-3x + 8y - 4z) but a slightly improved presentation would be to extract -4 from the original expression. So, -12x + 32y -16z = -4(3x - 8y + 4z)

2(x - 2)(x - 4)

(x-3)(x-9) = 0

12x + 5 - 2x =(12x - 2x) + 5 =10x + 5 =5 (2x + 1)

3x3+12x = 3x(x2+4)

There is no rational factorisation to this expression.

6y

12x + 31 = 2x + 1710x = -14x = - 1.4

People also asked